Polinatian mothads and seed lornialion in pers - Tombolato, Antonio Fernando Caetano (Pesquisa Agropecuaria Brasileira, 2013)
In lhe Persimmon Breeding Program ol the lnslituto Agronômico de Campinas (IAC), Campinas, SP, Brazil, several intervarielal crosses of persimmon trees (Diospyros kaki, L) were made in Vive diflerent ways, including poilinalion control under natural condilions. With lhe objetive ot calculaling lhe influence of each lreatment on seed production, lhe manipulated flowers, fruits, and seeds were counted. The developing stage ol fiower and pollen quality influenced the number ol seeds produced, much higher than lhe production under naftjral conditions. The rate ol fecundation is improved when lhe pollen is applied on the receptive sfigma ol lhe open flower, contrary to the melhod ol controlled crosses, applied previously, which consisis On removing the petais ol floral buds unopened and applying lhe poilen on lhe stigma, resulting in reduced seed lormation. It was observed that in lhe absence ol pollinalion the flowers without petals can Inictity, but by parthenocarpy, since a large part ol lhe lnjits produced do not show any seeds.